PERTANGGUNGJAWABAN PIDANA TERHADAP PENYEBAR BERITA BOHONG (HOAX) DALAM PERSPEKTIF HUKUM PIDANA INDONESIA PASCA PEMBARUAN KUHP DAN UU ITE - Rahmat Giling; Siti Humulhaer; Nursalim; Mahmuddin; Dany Wahyu (Berajah Journal, 2026)
The era of digitalization, marked by the rapid development of information and communication technology, has brought significant transformations in patterns of social interaction within society. The ease of access to information through digital platforms, particularly social media, paradoxically has also triggered the proliferation of false information or hoaxes that threaten social stability, public order, and national security. This study analyzes the construction of criminal liability for perpetrators of spreading false information within the framework of Indonesian criminal law following the reform of the Criminal Code and the enactment of Undang-Undang Nomor 1 Tahun 2024 tentang Perubahan Kedua atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik. This research employs a normative juridical method using statute, conceptual, and case approaches. The results of the analysis indicate that criminal liability for the dissemination of hoaxes has undergone significant evolution with the reform of both substantive and procedural criminal law. The offense of spreading false information is now comprehensively regulated under the ITE Law 2024 as lex specialis, reinforced by provisions in the National Criminal Code concerning crimes against state security, public order, and fraud. The elements of the offense emphasize the presence of intent (dolus), the dissemination of electronic information, and the potential to cause public unrest or losses. However, law enforcement implementation still faces several challenges, including the complexity of digital evidence, the anonymity of perpetrators, and the necessity to balance legal protection with freedom of expression within a democratic rule-of-law state.